Misdiagnosis of Bipolar Disorder: Rare or Frequent? - Kaya, Suheda; Tasci, Gulay; Korkmaz, Sevda; Atmaca, Murad (Selcuk University, 2023)
Background: Much as there have been limited number of studies which have examined misdiagnosis of bipolar disorder, it is so difficult to say that there is enough systematic research to identify the diagnostic rate of bipolar disorder. In our literature search, we could not find any study in our country about misdiagnoses before diagnosis of bipolar disorder. Therefore, we planned our study. Methods: The present study was done at xxx University, School of Medicine, Department of Psychiatry. Patients who were from both out-patient and in-patient clinics were included in the study. After a selection process, 171 patients with bipolar disorder were enrolled. In this group of patients, misdiagnosis of bipolar disorder were investigated. Results: Of the patients, 56.14 % had misdiagnosis of bipolar disorder. The most frequent misdiagnosis was fetermined to be major depressive disorder (in fifty cases, 54.3%). Followings were schizoaffective disorder (in 18 cases, 24.3%), schizophrenia (in 13 patients, 24.3%), delusional disorder (in 13 patients, 24.3%), dysthymic disorder (in 10 cases, 15.9%), generalized anxiety disorder ((in 10 cases, 15.9%), obsessive compulsive disorder (in seven cases, 12.6%), paranoid personality disorder (in two cases, 4.1%). Conclusions: The results of the study suggest that bipolar disorder is frequently misdiagnosed and that the most frequent misdagnoses were major depressive disorder and following psychotic spectrum disorders. Clinicians should be aware of frequent misdiagnosis in patients with bipolar disorder. © 2023, Selcuk University. All rights reserved.
Bipolar Bozuklukta Önceki Yanlış Tanıların Sıklığı
Keywords: Bipolar disorder; misdiagnosis, frequency